Illness and Healing from a Korean Woman’s Intercultural Perspective - Jeong, Mi hyeon (Feminist theology, 2011)
In Korean culture, illness is frequently considered punishment for sin. In spite of the prevalence of Western medicine and advanced technologies, moral judgment is frequently confused with physical causality. There are certain religious dietary customs which people undertake in order to be healed. These customs are open to misinterpretation, and can become a basis for accusation, fear and guilt. Women and people of inferior social status are easily accused of being the cause of illness within families and society. The persecution of witchcraft in the medieval age developed from a similar mechanism: it is easier to scapegoat an individual or a small group than to take responsibility as an entire community. A religion that creates guilt and fear is not oriented towards health. Rather than being a blessing, it is, in fact, a problem. I consider whether religion is death or life oriented. Life giving energy for the sake of individual, as well as community, is an important component.